2016
DOI: 10.1111/jog.13147
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the inferior mesenteric artery for post‐partum hemorrhage with a vaginal laceration: A case with unusual collateral supply

Abstract: A 36-year-old primipara woman was referred to the interventional department for management of severe primary post-partum hemorrhage with a vaginal laceration after a normal vaginal delivery. Angiography revealed that the superior rectal branch of the inferior mesenteric artery was one of the origins of persistent vaginal bleeding following embolization of both uterine arteries. The patient was successfully treated by selective embolization without other complications. Our case report highlights that the inferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…As embolic materials, various materials including GSP, a microcoil, or NBCA, were used in IMA embolization in this study. Although permanent embolic materials, such as NBCA, seem advantageous for achieving devascularization more effectively than using temporary embolic materials such as GSP, as the patient in a previous literature report, 3 as well as our study patients in whom temporary embolic materials were used, all showed successful hemostasis without rebleeding. There have been no embolization-related complications, such as bowel ischemia, and therefore suggesting that selective TAE of the superior rectal artery from the IMA is usually safe.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…As embolic materials, various materials including GSP, a microcoil, or NBCA, were used in IMA embolization in this study. Although permanent embolic materials, such as NBCA, seem advantageous for achieving devascularization more effectively than using temporary embolic materials such as GSP, as the patient in a previous literature report, 3 as well as our study patients in whom temporary embolic materials were used, all showed successful hemostasis without rebleeding. There have been no embolization-related complications, such as bowel ischemia, and therefore suggesting that selective TAE of the superior rectal artery from the IMA is usually safe.…”
Section: Discussionsupporting
confidence: 64%
“…The most probable mechanism for superior rectal artery bleeding is injury to the rectal artery associated with birth canal expansion and laceration as well as extravasated blood through the torn lower uterine body, cervix or vagina. 3,5 The CT findings that the origin of the extravasated blood abutted the adjacent rectum in two patients in this study also suggest that the adjacent rectal wall was distended and injured. However, the absence of rectal bleeding in our study patients implies that the injury was not so severe to cause real rectal wall tear.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…They reported that the hemorrhage was controlled by the selective embolization of the distal branches of the IMA. Kim et al (17) reported a patient with massive PPH due to damage of the collateral network between the superior rectal branch of the IMA and the vaginal artery following vaginal delivery and they controlled the hemorrhage with embolization. Vascular pathologies must be considered in patients with PPH with a delayed onset.…”
Section: Discussionmentioning
confidence: 99%